Older adults' experiences of a community wellness program (Connect 60+) that focused on physical activity and social connections: a qualitative exploratory study - Weselman, Tammy; Naseri, Chiara; Vaz, Sharmila; Beilby, Janet; Garswood, Luke; O'Connell, Hilary; Hill, Anne-Marie (CSIRO PUBLISHING, 2022)
BACKGROUND: Being physically active and socially connected is positively associated with healthy aging. Older adults living in the community may be at risk of social isolation and reduced physical activity, especially in recent times due to COVID-19. There are many programs that offer opportunities for evidence-based physical activity or social connection; however, there is a lack of programs that include both. The objective of this study was to explore the lived experience of older adults who participated in Connect 60+ - a program that promoted exercise and social activities - delivered from a community hub that could be attended either in person or online. METHODS: A qualitative study that used descriptive phenomenology was conducted. A purposive sample of 13 older adults (age ≥65years) was recruited to take part in semistructured telephone interviews to discuss barriers and enablers to program engagement. Data were analysed using thematic analysis. RESULTS: The overarching theme was that participating in Connect 60+ was an enjoyable and encouraging experience for participants. The program enabled them to increase their physical activity and build social connections within their community. The main themes that enabled engagement were: (1) an enabling program design, (2) developing new connections in the community, and (3) experiencing motivation to engage. A few barriers were identified, including difficulties connecting online and lack of male attendance. CONCLUSIONS: Wellness programs delivered in community hubs may facilitate older adults to increase their engagement in both physical and social activity. The program appeared to impact positively on participants' motivation, with some participants reporting that they had sustained their behaviour changes since program completion. To address identified barriers, easy to use online technology is recommended, and strategies to promote male attendance.